RETHINKING BASIC TERMINOLOGY IN PROVERB RESEARCH: A COGNITIVE STUDY - Naciscione, Anita (Proverbium - Yearbook, 2015)
A closer look at terminology reveals the need to rethink some of the fundamental terms in the study of proverbs. My aim is to explore the basic terminology in paremiological research and raise awareness of the terms used. My approach is cognitive semantic. An essential aspect in proverb research is the choice of terminology that forms the conceptual framework for research: the terminology employed discloses part of the author’s conception of the phenomenon. In paremiology, attitudes to proverbs have differed greatly. Along with stable positive terminology used in paremiological research since the beginning of the 1930s (Taylor 1931; Whiting 1931; Mieder 1974, 1989, 1993), a number of negative terms have been introduced, displaying an overtly or covertly negative attitude. Most of the negative terms are metaphorical. Cognitively, the meaning of a metaphorical term is an integral part of the respective research concept (Gibbs [1994] 1999; Naciscione 2006, 2010). Negative terminology raises doubt about the correctness of choice of term. Proverbs have been branded as stereotypes (Moon 1998; Norrick 2007) and clichés (Kirkpatrick 1996b; Rees 1996; Moon 1998; Cresswell 2000; Hayden 2013). Proverbs are often referred to as quotations (Cram 1983; Norrick 2007). They are even called a hodge-podge, a fuzzy category whose “images often fail miserably as models for organizing our perceptions of current situations” (Norrick 2007). I view the use of negative terminology in proverb research as groundless and inappropriate. Proverbs form part of cultural folk heritage; they are retained in the collective long-term memory of a people. Linguistically, choice of research terms is closely linked with the basic linguistic and cognitive understanding of proverbs in both the system of language and proverbs in use. More clarity and consistency in terminology would make it easier to communicate a message and follow developments.